ALTERNATIF PEMILIHAN SHAMPO KEMASAN SACHET DI KALANGAN REMAJA PUTERI KOTA AMBON - Salhuteru, Andrie Ch. (Arthavidya Jurnal Ilmiah Ekonomi, 2015)
This study aims to determine the selection of an alternative brand ofshampoo sachet by teenage girls in the Ambon town. The population of this studywere teenage girls aged 13-19 years. Samples were as many as 60 young girls weretaken by convenience sampling technique. The research data was collected using aquestionnaire, and subsequently processed and analyzed using chi-square analysis.The calculation and analysis shows that teenage girls in the Ambon town have analternative option shampoo with a particular brand, and they have a choice of morethan one brand of shampoo. Shampoo brand choice based on functional benefitsand emotional benefits of various attributes attached to each brand of shampoo.Thus the use of advertising in the mass media provide benefits for marketers tocommunicate information about their products to consumers. However, the resultsof this study showed that there was no difference in the selection of alternativebrands of shampoo sachet teenage daughter in Ambon town.Keywords: Decision purchases, consumer attitudes, product attributes